2011
DOI: 10.1136/ard.2010.146530
|View full text |Cite
|
Sign up to set email alerts
|

A common SNP in the CD40 region is associated with systemic lupus erythematosus and correlates with altered CD40 expression: implications for the pathogenesis

Abstract: CD40 has been identified as a new susceptibility locus in Greek and Turkish patients with SLE. The rs4810485 minor allele T is under-represented in SLE and correlates with reduced CD40 expression in peripheral blood monocytes and B cells, with potential implications for the regulation of aberrant immune responses in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 46 publications
4
53
2
2
Order By: Relevance
“…These factors may have limited our analysis. An association between the minor T allele of rs4810485 and down-regulation of CD40 mRNA has been previously described (Vazgiourakis et al, 2011). However, conflicting results have been obtained regarding the rs1883832 SNP.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…These factors may have limited our analysis. An association between the minor T allele of rs4810485 and down-regulation of CD40 mRNA has been previously described (Vazgiourakis et al, 2011). However, conflicting results have been obtained regarding the rs1883832 SNP.…”
Section: Discussionmentioning
confidence: 76%
“…The CD40 SNPs rs1883832 and rs4810485 have been identified as susceptibility markers for this and other autoimmune diseases, such as GD (Tomer et al, 2002;Kim et al, 2003;Li et al, 2012), MS (Blanco-Kelly et al, 2010;Sokolova et al, 2013), and SLE (Vazgiourakis et al, 2011;Chen et al, 2015;Lee et al, 2015). In addition, several studies suggest that these polymorphisms affect CD40 expression at the mRNA and protein level (Jacobson et al, 2005;Vazgiourakis et al, 2011;Field et al, 2015;Wagner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 The associated SNPs of these genes for KD and these diseases are identical or belonging to the same SNP group of high linkage disequilibrium. By bioinformatics analyses integrating published GWAS results and information of gene expression, expression quantitative trait loci and epigenome, Farh et al suggested the importance of Blinage cells in KD pathogenesis.…”
Section: Development Of Genetic Research Findings Novel Insights Intomentioning
confidence: 99%